The Legal Standing of Living Wills as Notarial Deeds in the Indonesian Health Law System: A Study on the Legal Certainty of Refusal of Medical Treatment - Efrianza Efrianza; Ni Nyoman Putri Purnama Santhi (West Science Law and Human Rights, 2026)
A living will is a legal instrument that sets out a person's wishes regarding future medical treatment they wish to receive or refuse once they are no longer legally competent to give consent themselves. Law Number 17 of 2023 on Health regulates informed consent for medical procedures, but does not explicitly regulate the mechanism of an advance directive for future decisions, creating a normative vacuum that risks legal uncertainty for patients, families, and medical personnel. This study aims to examine the legal standing of living wills within the Indonesian health law system and to analyze the extent to which a notarial deed may serve as a valid and binding legal instrument for recording a living will. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. The findings indicate that a notarial deed, given its perfect evidentiary force under Articles 1868 and 1870 of the Indonesian Civil Code, holds considerable potential to strengthen the legal certainty and binding force of a living will compared with the medical consent forms currently used in hospitals. The study recommends a proposed legal construction (ius constituendum) that explicitly recognizes the living will in the form of a notarial deed as part of the national health law system.